Forage Brassicas Stockpiled for Fall Grazing: Yield and Nutritive Value. Issue 1 (8th January 2016) - Villalobos, Luis A.; Brummer, Joe E.
Abstract : Forage brassicas can potentially be used to extend the grazing season into the fall for beef cattle operations, thereby reducing input costs. Nine cultivars of forage brassicas were seeded on two planting dates, and their yield and nutritive value were measured for two fall harvest dates over 2 years in northern Colorado. Cultivars evaluated included three turnips ( Brassica rapa L.; Purple Top, Barkant, and Appin); three rapes ( Brassica napus L.; Winfred, Barnapoli, and Bonar); Groundhog radish ( Raphanus sativus L.); Major Plus swede [ Brassica napobrassica (L.) Mill.]; and Pasja hybrid (Chinese cabbage [ Brassica rapa subsp. chinensis (L.) Hanelt] × turnip hybrid). Dry matter (DM) yield, crude protein (CP), neutral detergent fiber (aNDF), and in vitro true digestibility (IVTD) were evaluated using a three‐way factorial treatment structure. Planting date was the overriding factor impacting DM yield with an overall reduction of 3770 lb/acre by delaying planting until mid‐August. Additional forage was also obtained by delaying the harvest date until mid‐November, but the increase was minor compared with yields obtained with earlier planting. The rapes tended to yield the highest when seeded in mid‐ to late July, but there were only minor differences among cultivars seeded in mid‐August. Fiber content of forage brassicas was low (19.0–25.2%), and CP content (18.6–25.5%) and IVTD (85.5–92.9%) were above the requirements for all classes and stages of beef cattle. Forage brassicas had minor changes in nutritive value during the fall, which makes them suitable for stockpiling when combined with lower‐quality forages to dilute their high nutrient content and thereby minimize the potential for rumen upset.